Is Ecuador Real Gross Domestic Product per Capita and Other Macroeconomic Variables Cointegrated? An Autoregressive Distribution Lag Bound Test Approach - Amaiquema, Jesser Roberto Paladines (International Journal of Economics and Financial Issues, 2017)
Ecuador is an oil exporter country but it is also an importer of oil derivatives products. In this research the relationship between its real gross domestic product (GDP) per capita and the oil price, gas price, inflation and total expenditure is studied, taking annual data of all from 1980 to 2015 by using the methodology of autoregressive distribution lag bound test. It is concluded it exists a long run relationship between variables and the speed of adjustment to any disequilibrium in the short run is corrected at an approximately rate of 85%. The model showed itself stable. In addition it was demonstrated that there is a causal relationship from all regressors selected except total expenditure to real GDP per capita according to the Toda-Yamamoto technique. Keywords: Autoregressive Distribution Lag, Toda-Yamamoto, Ecuador JEL Classifications: C32, 040, F20